KONSEP PENDIDIKAN ‘HADAP-MASALAH’ PAULO FREIRE DAN RELEVANSINYA BAGI PENDIDIKAN DI INDONESIA (Telaah Filosofis-Kritis atas Relasi Guru dan Murid di Masa Pandemi Covid-19) - Romanus Piter; Magnus Mitan (Aggiornamento, 2020)
Focus of this paper is a problem in the learning process applied in Indonesia today, especially in teacher-student relations. The goal to be achieved is to find solutions in the form of philosophical-critical ideas that are appropriate in the learning process at school or campus, especially with the Work From Home (WFH) system, in order to improve the quality of education in Indonesia. The methodology used is an analysis of the problems in the education system in Indonesia today using the concept of